Agrosilvopastura as a Planned Agricultural form System Towards Sustainable Agriculture in Southeast Aceh District - Aiva Viforit (Lembaga Pengembangan Kinerja Dosen, 2025)
Agroforestry is also a form of sustainable agriculture model. Agroforestry systems are formed of three main components, namely forestry, agriculture, and livestock. The agrosilvopastura system is the combination of woody components (forestry) with agriculture (annuals) as well as livestock on the same land management unit. The priority order of the most important alternative options for sustainable agriculture includes strengthening farmer institutions, developing a cadre of farmers/farmer groups aware of sustainable agriculture, and increasing demonstration activities for sustainable agricultural technology. Financial analysis shows that all agroforestry systems are economically viable, and agrosilvopastura provides the most inputs compared to agrosilnikultur and silvopastura. Erosion that occurs on agroforestry land agroforestry, especially agrosilvoculture in the buffer zone of Southeast Aceh District is not harmful because it is smaller than the allowable erosion (<30.6 tons/ha/yr). The total biomass and carbon of stands in agroforestry systems with agrosilvopastura type of 103.17 and 46.74 tons per hectare, respectively, are similar to the total biomass and carbon of stands in mangrove forests. carbon in Rhizophora apiculata mangrove forest with a density of 463 trees per hectare, which were 169.46 (biomass) and 47.08 (carbon) tons per hectare, respectively. Agrosilvopastura systems can play a role in mitigating floods compared to monoculture farming systems for each hectare of land for every 1 hour of work.